Hubungan Pola Makan Dengan Indeks Masa Tubuh Pada Remaja Putri Usia 12-16 di Pondok Pesantren As-Sa’idiyah Tambak Beras Jombang - Hikmah, Dafiatil; Wijaya, Arif; Roni, Faishol; Fatma Pratiwi, Tiara; Camelia, Dina (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2025)
Adolescence with the age of 12-16 is a process of growth and development of body capacity, heavy activity, rapid body growth. Therefore, it is necessary to measure body mass index (BMI) using body weight and height measurements. This study aims to determine the relationship between diet and body mass index in female adolescents aged 12-16 at the As-Sa'idiyah Tambakberas Jombang Islamic Boarding School. The type of research used is correlation analytic design using a cross-sectional approach. The population in this study were female adolescents aged 12-16 years with a total sampling of 70 respondents. The research instrument used was a questionnaire. The statistical test in this study used the Spearman rank. The results of the statistical test using Spearman rank with a significant value of p value = 0.006 < 0.5 means that H1 is accepted, which means that there is a relationship between diet and body mass index in adolescents aged 12-16 years.The results of the study indicate that there is a relationship between eating patterns and body mass index in female adolescents aged 12-16 at the As-Sa’idiyah Tambakberas Jombang Islamic Boarding School. It is hoped that further researchers can use a larger sample size and utilize new information media. Keywords: diet, body mass index, andolescent girls.